Validation and reliability test of Chinese language patient-reported impact of symptoms in schizophrenia scale - Xiao Lin; Hongjun Tian; Hongjun Tian; Lina Wang; Ranli Li; Xiaoyan Ma; Yun Sun; Ziyao Cai; Jing Ping; Langlang Chen; Chuanjun Zhuo; Chuanjun Zhuo; et al. (Frontiers in Psychiatry, 2023)
BackgroundPatient-reported outcomes, or subjective evaluations directly reflecting the patient’s views, feelings, and judgments, are now being used to evaluate the outcomes of care and treatment of people with schizophrenia. In this study, we used an updated tool, the patient-reported impact of symptoms in schizophrenia scale (PRISS), translated into Chinese languages to assess the subjective experiences of schizophrenia patients.ObjectiveThis study aimed to test the psychometrics of the Chinese languages PRISS (CL-PRISS).MethodThis study used the Chinese version of PRISS (CL-PRISS), acquired from the harmonized English-language version. A total of 280 patients enrolled in this study were asked to complete the CL-PRISS, the positive and negative syndrome scale (PANSS), and the World Health Organization Disability Assessment Schedule (WHO-DAS). Construct and concurrent validity was tested using the confirmatory factor analysis (CFA) and Spearman correlation coefficient, respectively. The reliability of CL-PRISS was tested using Cronbach’s α coefficient and the internal correlation coefficient.ResultsConfirmatory factor analysis (CFA) analysis demonstrated three major factors in CL_PRISS: the first factor is productive experiences, the second factor is affective-negative, and the third factor experiences. The factor loadings between items and factors ranged from 0.436 to 0.899 (RMSEA = 0.029, TLI = 0.940, CFI = 0.921). The correlation coefficient between the CL_PRISS and PANSS was 0.845, and between the CL-PRISS and WHO-DAS was 0.886. The ICC of the total CL_PRISS was 0.913, and Cronbach’s α was 0.903.ConclusionThe Chinese version of the PRISS (CL_PRISS) can be effectively used for assessing the subjective experience of Chinese patients with schizophrenia.